2022
DOI: 10.3390/biology11121690
|View full text |Cite
|
Sign up to set email alerts
|

Cryolipolysis on More than One Body Area Increases Lipid Peroxidation without Changing Lipid Profile and Inflammatory Markers

Abstract: In the present study, the effects of cryolipolysis on one and multiple body areas, assessing body composition, lipid profile and peroxidation and inflammatory markers were investigated. Twenty-five women aged between 20 and 59 years were randomly assigned to three groups: (1) control, (2) cryolipolysis on the abdomen and (3) cryolipolysis on the abdomen + flanks. Anthropometric measurements, bioimpedance and ultrasound were performed, as well serum lipid profile, lipid peroxidation markers (malondialdehyde and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Da Costa et al, 2022 8 carried out a study that addressed the evaluation of some blood inflammatory markers in women who underwent a CLL session. The results of the study demonstrated that such markers had not shown differences.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Da Costa et al, 2022 8 carried out a study that addressed the evaluation of some blood inflammatory markers in women who underwent a CLL session. The results of the study demonstrated that such markers had not shown differences.…”
Section: Discussionmentioning
confidence: 99%
“…The resource targets subcutaneous adipocytes, aiming to induce apoptosis without damaging other adjacent tissues. 3,4,8 Although several clinical and experimental studies confirm that CLL can reduce subcutaneous adipose tissue, [9][10][11] the mechanisms of action are not fully clarified. Two hypotheses are extensively discussed in the literature, the first being based on the reduction of subcutaneous adipose tissue without apoptosis through energy expenditure using lipid oxidation and thermogenesis after the application of cooling.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations